Determination of optimal conditions for laccase production by Pleurotus ostreatus using sawdust as solid medium and its use in phenol degradation - Baghdad Science Journal (مجلة بغداد للعلوم, 2012)
The ability of four local fungal isolates for extracellular laccase production has been tested with five grams 1:1(w/v) humidified sawdust as substrate in mineral salt medium. After 21 day of incubation at 25±1 ? C and using one mycelial plug (5mm), higher level of laccase activity (0.15U/ml) and specific activity (15U/mg) were observed by Pleurotus ostreatus in comparison with other fungal isolates. The results of optimum conditions for laccase production from selected isolate showed that, the maximum laccase activity (0.55U/ml) and specific activity (55U/mg) were obtained at moisture ratio 1:3 (w/v), using 3 mycelial plugs (5 mm), after 15 days incubation period at 25±1 ? C. The results of phenol degradation by crud laccase revealed that, 100% degradation of phenol occurred after 24 hr of incubation at 25 ? C using shaking water bath except at 200mg/l, the remaining phenol was 10.13%.